The Effect of Conventional and Minimum Tillage Practices on some Soil Properties in a Dryland Vineyard - Van Huyssteen, L.; Weber, H. W. (South African Journal of Enology and Viticulture, 2017)
Preliminary results of a long-term viticultural tillage experiment comprising two groups of treatments, are reported. These groups are (i) a group of "minimum" tillage practices having received no mechanical soil tillage at all, and (ii) a group of "conventional" tillage treatments according to long-established local practices by disc-harrow. The "minimum" group consists of: (a) a permanent straw mulch cover, (b) chemical weed control, and ( c) a permanent cover of indigenous weeds frequently cut by a bush-cutter. The "conventional" group consists of: (a) deep and (b) shallow trench furrow systems, and (c) the locally customary "clean cultivation" system. A comprehensive investigation into the changes of sleeted soil properties after a period of eight years revealed significant differences between properties of the soil under minimum tillage (group (i)) and under clean cultivation (group (ii)). Soil parameters, such as pore volume distribution, compaction indices, activity of micro-organisms and availability of plant nutrients, were found to be more favourable in some minimum tillage treatments than on the conventionally tilled plots.